GENDER-BASED ROLES AND PERFORMANCE ON IRISH POTATO (SOLANUM TUBEROSUM L.) PRODUCTION IN CENTRAL AGRICULTURAL ZONE OF PLATEAU STATE, NIGERIA - Matawal, O.M. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study examined gender-based roles and performance of Irish potato (Solanum tuberosum L.) production in the Central Agricultural Zone of Plateau State, Nigeria. A multistage sampling technique was used in selecting 100 respondents for the study. Data were collected using a structured questionnaire and analyzed using descriptive statistics and a t-test. The findings revealed that all of the Irish potato production activities were performed by both sexes, but their level of involvement varied it showed that most (99.1%) of the male respondents were involved in land preparation while 98.9% of the females were involved in land preparation. It implies that male Irish potato farmers slightly performed more tasks than female in terms of land preparation in the study area. In ridging, results showed that 96.3% of the male farmers participated while 82.6% of female engaged in ridging activities. Emanating from the findings it can be concluded that male dominated most farming activities and had more access to production resources like land, capital and labour compared to their female counterparts. The study concluded that male Irish potato farmers dominated farming activities such land preparation, ridging, weeding, planting, fertilizer application and harvesting among others and had more access to production resources compared to women in the study area. The study recommends that government and non-governmental organizations should provide training and credit facilities to female farmers to boost their productivity and reduce the gender gap in performance.